A Study on Hadith Authenticity Concerning the Abrogation of Bequests for Iddah Maintenance by Heirs and Its Relevance to Islamic Family Law in Indonesia - Aniroh, Reni Nur; Zinira, Maurisa (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
Although Islamic jurists (fiqh scholars) have reached a consensus on the elimination of the provision for iddah maintenance (post-divorce or mourning period support) through inheritance shares upon a husband’s death, the hadith cited as the basis for this elimination remains a subject of debate. This consensus carries sociological, legal, and theological implications that may disadvantage wives, particularly in the aftermath of their husbands' deaths. The purpose of this study is to reassess the authenticity of the hadith concerning the elimination of iddah maintenance via inheritance distribution. This paper employs Abou El Fadl's hermeneutic negotiation approach to scrutinize the authenticity of the hadith regarding the elimination of iddah maintenance and to contextualize it within the Indonesian framework. The findings indicate that the hadith serving as the foundation for this issue is an attributed to a companion rather than the Prophet (mauquf hadith), whose chain of narration (sanad) is contested. Certain narrators are considered unreliable, and there are discrepancies within its text (matn), with multiple versions existing. Consequently, this paper refrains from relying on the doctrine of abrogation (naskh) and supports the view that iddah maintenance following a husband’s death is an option that need not conflict with the wife’s inheritance share. Both iddah maintenance and the wife’s inheritance share can thus be implemented concurrently. The paper posits that, in the Indonesian context, iddah maintenance upon the husband’s death should be regarded as a form of joint property that can be allocated without reducing the wife’s inheritance share. The implementation of both joint property distribution and inheritance safeguards the rights of the wife and her children following the husband's death.